Application Of The Steam Method With Loose Parts To Stimulate Critical Thinking In Children Aged 5-6 Years At Aisyiyah Bustanul Athfal Iv Kindergarten, Sidoarjo: Penerapan Metode Steam Dengan Loose Parts Dalam Menstimulus Critical Thinking Pada Anak Usia 5-6 Tahun Di Taman Kanak Kanak Aisyiyah Bustanul Athfal Iv Sidoarjo - Dinda Nurmala; Luluk Iffatur Rocmah (Academia Open, 2024)
Learning that provides space for children to be able to solve problems and make decisions independently is one of the learning strategies that can be used to improve children's critical thinking skills. The STEAM method is a reform in the world of education that combines science, mathematics in order to have a logical and rational mindset, so that children can understand phenomena critically and logically. The research was carried out by conducting direct observation in learning activities in the classroom. Then the results of the observations were corroborated by interviews conducted with school principals, class educators and students who directly played a role in the process of implementing the STEAM method with Loosepart. Data analysis in this research uses analysis which includes three stages, namely data reduction is the process of selecting, focusing on simplification, abstracting and transforming raw data that emerges from written records in the field. In stimulating children's critical thinking, educators provide opportunities to observe and explore the tools and materials in front of them with various senses. So that children are encouraged to be more curious about what they will do with various tools and materials. In this way, critical thinking in children can be stimulated so that children have the ability to ask questions and find out about information and observe and explore the tools and materials around them, they also have the ability to solve problems through play activities, and have the confidence to make decisions. in carrying out their activities. Highlights: Interdisciplinary Approach: STEAM method integrates science, technology, engineering, arts, and mathematics, fostering a holistic and logical mindset in children. Loose Parts Play: Utilizing loose parts in learning activities stimulates curiosity, encouraging children to explore and solve problems independently. Observation and Exploration: Educators play a crucial role in providing opportunities for children to observe, explore, ask questions, and make decisions, fostering critical thinking skills. Keywords: STEAM method, Loose parts, Critical thinking, Kindergarten